Alternative development and the role of commercial handicraft production in Sarawak, Malaysia. - Berma, Madeline (Universiti Kebangsaan Malaysia, 2001)
The objective of this paper is to discuss the role of commercial handcraft production in solving some of the rural problems which have resulted from increasing poverty, environmental degradation and cultural alienation in Sarawak, Malaysia. The analysis is based on an in-depth study conducted between 1993 to 1996 of 200 Iban crafpersons from eleven rumah panjang (longhouses) in Kapit Division, Sarawak. One of the major findings of this study is that rural Iban involvement in handicraft production could become an important element for a future process of small-scale industrialisation in-situ. Handicraft production is generally environmentally-friendly, labour-intensive, and most importantly it uses local resources (such as skills, institutions, and raw materials). With Sarawak's growing emphasis on tourism development and the rich cultural heritage of the Iban, the expansion of commercial handicraft production provides an 'alternative' development path for the state.